(untitled) (Jurnal Studi Inovasi Pemerintahan, 2025)
In Kayu Agung Village, the Implementation of the Village Development Planning Deliberation faces a few significant problems, one of which is the low level of active community participation. In addition, the presentation of information by the BPD is inadequate on the principles of democracy in the Musrembang, which has not been directed at the right target. Therefore, the purpose of this study is to determine how the implementation of the principles of deliberative democracy in the village Musrembang. This study uses the theory of deliberative democracy from Jurgen Hubermash. This study uses qualitative methods and a descriptive approach. Descriptive research is a type of research that aims to provide a complete picture of a phenomenon by describing variables related to the problem being studied. Data collection through informant interviews and observations originating from the Kayu Agung Village Government, and its staff, Religious Leaders, Youth Leaders, Women Leaders, and Community Leaders. In addition, this study is also supported by reports and documents related to the topic. The results of this study indicate that the implementation of the Village Development Planning Deliberation (Musrenbangdes) in Kayu Agung Village has not been fully implemented consistently in Kayu Agung Village. Community participation in the Village Development Planning Deliberation (Musrenbang Desa) in Kayu Agung Village reflects the collective awareness of residents towards village development. However, the implementation of the principle of participation still faces serious challenges, thus reducing the essence of deliberative democracy. This study is expected to add to the literature related to the implementation of the Village Development Planning Deliberation carried out by the village government in the Parigi Moutong district.